Gizzard erosion in chickens - Metin Münir Kıran; Şenay Berkin; İbrahim Çetin (Eurasian Journal of Veterinary Sciences)
In this study, gizzard erosion was investigated in twelve 4-5 weeks old chickens. The mortality rate was determined as 7 per cent.